Social norms in digital spaces: Conflict reports and implications for technology design in the teleworking context - Sarah Diefenbach (Zeitschrift für Arbeitswissenschaft, 2022)
With the increase of telework during the COVID-19 pandemic, employees' interactions with colleagues have shifted almost exclusively to digital channels. Hence, it is critical to understand the underpinnings of successful collaboration and individual wellbeing in digital working structures. Combining qualitative experience reports and quantitative surveys from 145 teleworkers, this study sheds light on teleworking from a~psychological perspective, taking social norms as a~conceptual frame. The qualitative reports revealed five types of typical conflicts related to communication in the telework context, including both (1)~technical problems (e.g., a~bad connection) and psychological aspects such as (2)~uncertainty or a~lack of social feedback, (3)~norm violations, (4)~a~lack of rules or meta-communication about appropriate behavior, and (5)~digital communication barriers. Respondents' quantitative ratings of qualities of telework versus working on-site revealed benefits of telework regarding task fulfillment and efficiency, but lower levels of motivation, conflict management, leadership, team spirit, inspiration and creativity. Participants qualitative reports on perceived challenges in remote work conditions included feelings of loneliness and increased demands related to self-management, creating boundaries between private and working life, motivation and self-regulation. This paper connects these findings with theoretical concepts from psychology and human-computer interaction and discusses implications for leadership and technology design. Practical Relevance : This article discusses practical implications for leadership and technology design, e.g., interventions against conflicts in the context of digital work. – – Mit der Zunahme von Telearbeit im Zuge der COVID-19-Pandemie hat sich die Interaktion mit Kollegen im Arbeitskontext fast ausschließlich auf digitale Kanäle verlagert. Ein umfassendes Verständnis der Grundlagen erfolgreicher Zusammenarbeit und individuellen Wohlbefindens in digitalen Arbeitsstrukturen gewinnt somit zunehmende Relevanz. Die vorliegende Studie [ N =0.167em145] beleuchtet Telearbeit aus psychologischer Perspektive anhand einer Kombination von qualitativen Erfahrungsberichten und quantitativen Ratings und nutzt das Konzept sozialer Normen als konzeptionellen Rahmen. Eine Kategorisierung der qualitativen Konfliktberichte ergab fünf typische Konflikten im Zusammenhang mit der Kommunikation im Telearbeitskontext, darunter (1)~technische Probleme (z. B. schlechte Verbindung) als auch psychologische Aspekte wie (2)~Unsicherheit/fehlendes soziales Feedback, (3)~Normverletzungen, (4)~Mangel an Regeln und Metakommunikation über angemessenes Verhalten und (5)~Kommunikationsbarrieren in digitalen Strukturen. Die quantitativen Ratings der Befragten Arbeitsqualitäten von Telearbeit im Vergleich zur Vor-Ort-Arbeit zeigten Vorteile von Telearbeit in Bezug auf Aufgabenerfüllung und Effizienz, jedoch ein geringeres Maß an Motivation, Konfliktmanagement, Führung, Teamgeist, Inspiration und Kreativität. Qualitative Berichte bezüglich wahrgenommener Herausforderungen der Home-Office-Situation bezogen sich auf Gefühle der Einsamkeit und erhöhte Anforderungen in Bezug auf Selbstmanagement, Abgrenzung zwischen Privat- und Arbeitsleben, Motivation und Selbstregulierung. Der vorliegende Beitrag diskutiert diese Ergebnisse in Verbindung mit theoretischen Konzepten aus Psychologie und Mensch-Computer-Interaktion und erörtert Implikationen für Führung und Technikgestaltung. Praktische Relevanz : In diesem Artikel werden praktische Implikationen für Führung und Technologiegestaltung erörtert, z. B. Interventionen gegen Konflikte im Kontext der digitalen Arbeit.
Keywords: 650; Telework; Digital space; Digital communication; Home office; Wellbeing; Social norms; Technology design; Telearbeit; Digitale Räume; Digitale Kommunikation; Wohlbefinden; Soziale Normen; Technikgestaltung